An introduction to the Delphi method. (SAGE Publications Ltd, 2017)
Dr Mithu Bhattacharya discusses Delphi research method. This method is used when little hard data or established theory is available on a given topic. It aggregates judgments from several subject-area experts, whose participation is anonymous.